PRODUCTION AND DEVELOPMENT OF NUTRACEUTICALS USING BACILLUS SUBTILIS NCIM 2708 UNDER SOLID STATE FERMENTATION BY RESPONSE SURFACE METHODOLOGY - Ahmad, Md Faruque; Ashraf, Syed Aamir; Azad, ZR Azaz Ahmad; Panda, Bibhu Prasad (European Scientific Journal, ESJ, 2013)
Nutraceuticals is a broad umbrella term used to describe any product derived from food sources that provides further health benefits in addition to the essential nutritional value found in foods intense interest the public towards worth full effect not only for medicinal but also as a nutraceutical products. This research aimed to maximize production of Menaquinone-7(MK-7) by solid state fermentation process. Menaquinone-7 (MK-7) was produced by solid state fermentation process of Glycine max and Phaseolus vulgaris in presence of a co-cultured by Bacillus subtilis. Three separate nutritional parameters were screened for each experiment for the production of MK-7 using Plackett–Burman experimental design. Parameters were optimized by Box–Behnken design of response surface methodology for the production of menaquinone-7 (MK-7). In present study, 16.39 μg MK-7 produced per gram of Glycine max in optimised formula in the medium contains sorbitol 51.22g kg־1, urea- 3.40g kg־1 and MnCl2-0.20g kg־1. With Phaseolus vulgaris 31.35 μg of MK-7 produced per gram of the substrate in a optimised media containing glycerol-54.05g kg־1, urea-3.40g kg־1 and soybean extract-15.00g kg־1.